Diagnostic Utility of CD10, EMA and BCL2 Markers in Differentiating Between Squamous Cell Carcinoma and Basal Cell Carcinoma of Skin - Khadija, Shafaq (International Journal of Pathology, 2022)
Introduction: Non Melanocytic Skin Cell Carcinomas are the commonest malignancies among aucasians. According to a study conducted 59.5% BCC cases showed CD10 positivity whereas 100% SCC cases showed negativity. Expression of Bcl-2 found positive in 96.5% of BCC cases and 100% negative in SCC. Studies demonstrate EMA to be positive in 100% cases of SCC while showing 100% negativity for BCC. Differentiating BCC from SCC on the basis of IHC is vital as both have diverse managements based on their different prognosis, metastasis and recurrence. Objectives: To study expression of CD10, BcL2 and EMA in BCC and SCC and correlate this expression in differentiating between BCC and SCC. Methods: Study had 64 samples taken from 1st September 2018 - 31st August 2019 at department of Histopathology, PIMS, SZABMU, and Islamabad. After H&E staining, IHC was done with CD 10, EMA and Bcl 2 markers and the results evaluated. Results: CD10 showed positivity in 81.6% of BCC cases and negativity in 84.8% cases of the SCC. Bcl2 immunoreactivity was seen in 84.4% BCC cases whereas SCC showed negativity in 84.9% cases. Considering immune-expression of EMA in SCC 90.6% cases showed positive staining; only 9.4% cases were negative for EMA. 96.9% cases of BCC were negative for EMA. Conclusion: We suggest that concurrent application of CD10, BCL2 and EMA Immuno markers has high diagnostic value where distinction between BCC and SCC cannot be made on routine microscopy.